Pore pressure migration during hydraulic stimulation due to permeability enhancement by low‐pressure subcritical fracture slip - Yusuke Mukuhira; Hirokazu Moriya; Takatoshi Ito; Hiroshi Asanuma; Markus Häring (Geophysical Research Letters)
Abstract Understanding the details of pressure migration during hydraulic stimulation is important for the design of an energy extraction system and reservoir management, as well as for the mitigation of hazardous‐induced seismicity. Based on microseismic and regional stress information, we estimated the pore pressure increase required to generate shear slip on an existing fracture during stimulation. Spatiotemporal analysis of pore pressure migration revealed that lower pore pressure migrates farther and faster and that higher pore pressure migrates more slowly. These phenomena can be explained by the relationship between fracture permeability and stress state criticality. Subcritical fractures experience shear slip following smaller increases of pore pressure and promote migration of pore pressure because of their enhanced permeability. The difference in migration rates between lower and higher pore pressures suggests that the optimum wellhead pressure is the one that can stimulate relatively permeable fractures, selectively. Its selection optimizes economic benefits and minimizes seismic risk.